2006
DOI: 10.2337/diacare.29.03.06.dc05-1396
|View full text |Cite
|
Sign up to set email alerts
|

Depression Treatment and Satisfaction in a Multicultural Sample of Type 1 and Type 2 Diabetic Patients

Abstract: OBJECTIVE—To assess rates of depressive symptoms, depression treatment, and satisfaction in a multicultural sample of individuals with type 1 and type 2 diabetes. RESEARCH DESIGN AND METHODS—This study was conducted with a cross-sectional community-based survey design. RESULTS—The sample (n = 221) was predominantly female (60.3%), had type 2 diabetes (75%), and was middle class with a mean (±SD) age of 54 ± 12 years. A total of 53% were white. Depressive symptoms were assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 30 publications
5
28
1
Order By: Relevance
“…5 Specifically, the prevalence rate of clinical depressive symptoms among South Texas respondents in our study was also higher than those reported in studies conducted with older Mexican Americans in Southwestern states (25.6% to 31.1%) 40,41 or Hispanic adult patients (31.6%), 6,23 but similar to a study with Hispanic women in South Florida (40.6%). 24 In the case of our border sample from the Mexican side, the clinical depressive symptoms prevalence rate found was similar to previous studies conducted in Central Mexico (37.91% to 39%) 25,42 but inconsistent with another study from Mexico City (46%).…”
Section: Discussioncontrasting
confidence: 55%
“…5 Specifically, the prevalence rate of clinical depressive symptoms among South Texas respondents in our study was also higher than those reported in studies conducted with older Mexican Americans in Southwestern states (25.6% to 31.1%) 40,41 or Hispanic adult patients (31.6%), 6,23 but similar to a study with Hispanic women in South Florida (40.6%). 24 In the case of our border sample from the Mexican side, the clinical depressive symptoms prevalence rate found was similar to previous studies conducted in Central Mexico (37.91% to 39%) 25,42 but inconsistent with another study from Mexico City (46%).…”
Section: Discussioncontrasting
confidence: 55%
“…The need for longitudinal studies was a frequently repeated recommendation by several researchers (Ciechanowski et al, 2000;De Groot et al, 2006;Finkelstein et al, 2003). Many researchers recommend further studies to determine the effectiveness of the treatment of depression on the cost and burden of diabetes care (Egede et al, 2002;Katon et al, 2004;Lin et al, 2004;Ludman et al, 2004;Simon et al, 2005).…”
Section: Discussion and Recommendationsmentioning
confidence: 95%
“…The total CES-D score ranges from 0 to 60, a score >16 indicates a clinically relevant depression [34]. The overlaps with symptoms originating from a physical illness are limited; the CES-D has been proved to be a valid instrument in the physically ill [35], including patients with rheumatoid arthritis [36] and diabetes [37]. …”
Section: Methodsmentioning
confidence: 99%